Nanocrystalline TiO2 Electrodes Exhibiting High Storage Capacity and Stability in Rechargeable Lithium Batteries - Sui-Yang Huang; Ladislav Kavan; Andreas Kay; Michael Grätzel; Ivan Exnar (Active and Passive Electronic Components)
Nanocrystalline TiO2 films were explored for the first time as electrode material for a rechargeable lithium intercalation cell, i.e., Li/LiCF3SO3 + PC/TiO2. Two kinds of nanocrystalline films, TiO2 F387 (Degussa) and TiO2 colloid-240, were investigated. These films exhibited excellent performance renderings them a promising choice for secondary battery applications. At a current density of 0.01 mA/cm2, two voltage plateaus at 1.78 and 1.89 V were observed for TiO2 F387 films during charge and discharge, respectively. The TiO2 electrode charge capacity per unit weight rose with decreasing current density. The highest capacity, obtained at a current density of 0.005 mA/cm2 and a final discharge voltage of 1.4 V, was 265 mAh/g corresponding to a lithium insertion ratio of x = 0.8. Nanocrystalline TiO2 colloid-240 films showed a similar performance. The cycle life of a TiO2 colloid-240 cell at a high current density was found to be excellent; a capacity loss lower than 14% has been observed over 100 charge/discharge cycles.